(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
Economic growth represents a goal and an obsession that all countries strive to achieve and search for means and factors that would improve it and increase its rates, and one of the most important indicators that reflect the standard of living of individuals. Economic growth is the outcome of a complex and intertwined process. The prepared research aims to: shed light on the most important determinants of economic growth in Syria for the period of time (1978 - 2019), identify the overall total productivity of production factors, through a presentation on the most important theories that dealt with the process of economic growth and the total productivity of production factors, and review & analysis of the most important economic variables in Syria (GDP - capital formation - employment...) in a statistical way that defines the determinants of economic growth and the overall productivity of production factors in Syria. An emphasis was also placed on the features and characteristics of the current stage, especially in terms of the repercussions of the global war on Syria, the results of the sabotage acts of terrorist groups, in addition to the economic sanctions imposed on them.